Creating a Culture of Wellness: A Call to Action for Higher Education, Igniting Change in Academic Institutions - Megan Amaya; Teresa Donegan; Debbie Conner; Julie Edwards; Christy Gipson (The Ohio State University Libraries, 2019)
Background: Due to the continued rise of chronic conditions and unhealthy lifestyle choices, more innovative and evidence-based practices are needed for students, faculty and staff to improve population health outcomes and enhance overall well-being.  Aim: The purpose of this paper is to inform academic health promotion professionals of key strategies to consider in order to create cultures of wellness on their college campuses.  Methods: A review of the existing literature was conducted. Results: The most current evidence-based practices to create a culture of wellness are discussed. Conclusions:Institutions of higher education have an opportunity to create campus cultures that foster health and well-being. The time is now for enacting change to create, improve, or sustain cultures of wellness within campus communities.